The addition of neoadjuvant pertuzumab for the treatment of HER2+ breast cancer: A cost estimate with real-world data - Andreia Borges; Filipa Pereira; Patrícia Redondo; Luís Antunes; Cláudia Vieira; Pedro Antunes; Maria José Bento; Susana Sousa; José Machado Lopes; Francisco Rocha-Gonçalves; Joaquim Abreu de Sousa; Deolinda Sousa Pereira; et al. (Health Economics Review, 2021)
Background: Breast cancer (BC) is largely prevalent worldwide. HER2-positive BC account for roughly 20-25% of all BC cases and has an overall survival lower than other BC. Innovation on BC therapeutics is a constant, but novel therapies have higher costs. Therefore, cost-effectiveness research is essential to provide healthcare decision-makers with solid foundations for a resource allocation. This study aims to estimate the average direct medical costs/ patient and cost-effectiveness of adding pertuzumab in neoadjuvant treatment (NeoT) for HER2-positive breast cancer (BC). Methods: Two retrospective real-world consecutive cohorts of ≥18yo female patients diagnosed with HER2- positive BC treated with NeoT at the Breast Clinic of IPO-Porto were studied. The AC-DH regimen (2012-2015) comprised 8 cycles of neoadjuvant therapy (4 cycles of doxorubicin + cyclosphosphamide followed by 4 cycles ofdocetaxel + trastuzumab), while the AC-DHP regimen (2015-2017) included also pertuzumab as NeoT. NeoT was followed by surgery and adjuvant trastuzumab. Micro-costing technique and a bottom-up approach was used comprising all medical direct costs from the hospital perspective. Unit costs were obtained from government official prices or from IPO-Porto costing system. Costs were adjusted to 2017 and are expressed in euros. Multivariable logistic regression models were used for effectiveness assessment, while generalized linear models with gamma distribution were used for costs. ICER was calculated using the pathological complete response (pCR) as the preferential measure of effectiveness. Sensitivity analysis was also performed. Results: AC-DHP (n = 40) and AC-DH (n = 54) cohorts had heterogenous patient profiles (median age 43y/53y; 67.5%/59.3% positive HR; 60.0%/27.8% operable; 25.0%/24.1% inflammatory, respectively). The AC-DHP average total cost/patient was 56,375 exteuro, with pertuzumab accounting for 13,978 exteuro (24.79%) and increasing in 15,982 exteuro the average cost/patient (p < 0.001). Clinical staging and hormone receptors (HR) were significantly associated with pCR. ICER was 1.370 exteuro per percentage point of pCR. Conclusions: ICER was more favourable in stage III HR negative BC patients compared to other patient profiles. Innovative treatments access is critical to deliver high-quality healthcare, but sustainability must be considered. These results suggest the importance of establishing a cost-effectiveness profile of Pertuzumab in NeoT for HER2- positive BC.
Keywords: 330; Pertuzumab; Neoadjuvant treatment; HER2-positive breast cancer; Cost-effectiveness analysis